Auditoría de Gestión al departamento de presupuesto del Grupo de Fuerzas Especiales No. 26 “CENEPA”, periodo 2023 - Asunción Ramírez, Maribel Jacqueline (2024)
Management auditing in public institutions provides valuable information for decision- making. Therefore, the present research, titled “Management Audit of the Budget Department of the Special Forces Group No. 26 Cenepa, Period 2023,” aims to evaluate the efficiency, effectiveness, and economy of the allocated budget, highlighting strengths and areas for improvement, based on theories of public management and internal control. Additionally, it focuses on identifying deficiencies in staff training and budget planning. A mixed-methods approach was employed, combining qualitative and quantitative analysis to obtain a comprehensive view of the current state of management in the institution. The research design was descriptive and exploratory, allowing for a detailed evaluation of current practices and the development of recommendations to improve operational efficiency. Data collection techniques included interviews, questionnaires, and document reviews, all designed to assess compliance with internal control standards and the effectiveness of training and budget planning processes. The main results revealed a budget execution rate of nearly 99.99%, but also identified a lack of trained and specialized personnel and the absence of recent management audits. Furthermore, underutilization of resources was detected during the first four months of the year, indicating problems with budget planning. In conclusion, the study highlights the urgent need to stabilize staff, improve ongoing training, and establish regular audits. These actions are essential to ensuring efficient and transparent financial management, which is crucial to the operational success of the Special Forces Group No. 26 "CENEPA." The implementation of these recommendations will strengthen the institution's capacity to face future challenges and meet its strategic objectives.